The effect of fatty acids, ionic strength, and electric fields on the microscopic dynamics of BSA aggregates - Kang, Kyongok (Frontiers in Physics, 2023)
This paper presents microscopic dynamics of the concentrated suspensions of Bovine Serum Albumin (BSA) proteins and their aggregates by dynamic light scattering (DLS) experiments. The effects of fatty acids binding to BSA, as well the ionic strength and weak electric field are discussed for affecting the stability of BSA suspensions against calcium-induced aggregation. By variation of the ionic strength, in the absence of external electric field, DLS-experiments show that monomer BSA interactions (in the case of essentially fatty acid free) are overall repulsive, but that nevertheless aggregation occurs to some extent. Also, the diffusive properties of different types of BSA are explored under an applied low AC electric field by means of in-situ electric small-angle depolarized DLS-experiments, which reveal a significant decrease of the translational BSA-monomer diffusion coefficient with increasing frequency, while the aggregates indicate orientational motion via rotation on applying an electric field. These observations are interpreted in terms of (localized) orientation interactions that obtained as oscillations in the intermediate scattering correlation function, as well the anomalous slower relaxations as resulting effective (collective) dynamics between monomeric BSA and their protein aggregates.